Potential of Cellulose from Sugarcane Bagasse as a Bioplastic Material for Drug Capsules - Agustina, Eva; Erfansyah, Nasrul Fuad; Lusiana, Nova; Purnamasari, Risa (State Islamic University of Sunan Ampel, 2026)
Sugarcane bagasse is a lignocellulosic waste that has significant potential as a cellulose source for the development of environmentally friendly bioplastics. This study aims to This study aimed to evaluate the potential of cellulose derived from sugarcane bagasse as a bioplastic material for drug capsule applications.. The research method includes the isolation of sugarcane bagasse into cellulose and the production of bioplastics. The bioplastics were prepared in two formulations, namely P1 (without cellulose) and P2 (with the addition of sugarcane bagasse cellulose), using chitosan as the polymer matrix and glycerol as a plasticizer. Characterization was conducted through morphological analysis, mechanical properties (tensile strength and elongation), density, thickness, water absorption, and biodegradability tests. Statistical analysis using an independent samples t-test revealed significant differences between formulations. The tensile strength of P2 (39.2 MPa) was significantly higher than P1 (21.5 MPa) (t = 13.7, p < 0.001), while elongation significantly decreased from 27.58% in P1 to 17.32% in P2 (t = 10.9, p < 0.001). Density and thickness also increased significantly in P2 (0.8444 g/cm³ and 0.276 mm) compared to P1 (0.5396 g/cm³ and 0.118 mm) (t = 10.5 and 18.3; p < 0.001), indicating a more compact film structure. In contrast, water absorption showed no significant difference between treatments (t = 0.10, p = 0.92), and both samples exhibited similar biodegradation times of approximately four days (t = 0.00, p = 1.00). These result demonstrate that cellulose incorporation improves mechanical strength and structural compactness without reducing biodegradability. Cellulose-based bioplastic derived from sugarcane bagasse has the potential to be developed as an alternative soft capsule material in environmentally friendly drug delivery systems, serving as a substitute for gelatin-based capsules in the pharmaceutical industry.